2020
DOI: 10.1103/physrevx.10.031021
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Magnetohydrodynamic Modes in Compressively Driven Plasma Turbulence

Abstract: We study properties of magnetohydrodynamic (MHD) eigenmodes by decomposing the data of MHD simulations into linear MHD modes-namely, the Alfvén, slow magnetosonic, and fast magnetosonic modes. We drive turbulence with a mixture of solenoidal and compressive driving while varying the Alfvén Mach number (M A), plasma β, and the sonic Mach number from subsonic to transsonic. We find that the proportion of fast and slow modes in the mode mixture increases with increasing compressive forcing. This proportion of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 55 publications
10
47
0
Order By: Relevance
“…For example, characteristics for three separate propagating linear eigenmodes – the Alfvén mode, the slow magnetosonic mode and the fast magnetosonic mode have been studied using numerical simulations (Cho & Lazarian 2002; Kowal & Lazarian 2010; Yang et al. 2018; Makwana & Yan 2020) and observations (Yao et al. 2011; Howes et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, characteristics for three separate propagating linear eigenmodes – the Alfvén mode, the slow magnetosonic mode and the fast magnetosonic mode have been studied using numerical simulations (Cho & Lazarian 2002; Kowal & Lazarian 2010; Yang et al. 2018; Makwana & Yan 2020) and observations (Yao et al. 2011; Howes et al.…”
Section: Introductionmentioning
confidence: 99%
“…A decomposition of the turbulent field is frequently implemented to study different compressible MHD turbulence processes. For example, characteristics for three separate propagating linear eigenmodes -the Alfvén mode, the slow magnetosonic mode and the fast magnetosonic mode have been studied using numerical simulations (Cho & Lazarian 2002;Kowal & Lazarian 2010;Yang et al 2018;Makwana & Yan 2020) and observations (Yao et al 2011;Howes et al 2012;Klein et al 2012). In this work, we decompose the velocity field into solenoidal and compressive parts following Helmholtz decomposition as used in Kida & Orszag (1990, 1992, Miura & Kida (1995), Pan & Johnsen (2017), Wang et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence & Cosmic ray propagation Huirong Yan magnetic pressure, the magnetosonic modes should be considered when studying such turbulence. Studies have shown that the energy spectrum and the scale-dependent anisotropy of slow modes are quite similar to Alfvén modes [24,25,29]. On the other hand, fast modes seem to show an isotropic cascade.…”
Section: Pos(icrc2021)038mentioning
confidence: 98%
“…Our view on the transport of CRs has been rapidly changing, largely thanks to the advances in MHD turbulence [7,8]. MHD turbulence can be decomposed and the interaction of turbulence with CRs can be studied separately in each of the three MHD modes, Alfven, fast and slow, the latter of two are compressible modes [24,25]. It has been demonstrated based on the tested model of turbulence that the scattering of CRs ( 100 GeV) is dominated by fast modes instead of the often-adopted Alfven modes, which indicates the inhomogeneous scattering of CRs [19,20,23] and inefficiency of scattering on low energy CRs.…”
Section: What Do We Know About Turbulence Now?mentioning
confidence: 99%
“…Particle scattering and diffusion largely rely on the properties of plasma turbulence. Fast modes waves show an isotropic cascade and it could be the most effective scatterers of cosmic-rays [3]. The spectrum of the isotropic cascade was claimed to be k −3/2 .…”
Section: Introductionmentioning
confidence: 99%